2010
DOI: 10.1088/0004-637x/718/1/23
|View full text |Cite
|
Sign up to set email alerts
|

THEXMMCLUSTER SURVEY: THE BUILD-UP OF STELLAR MASS IN BRIGHTEST CLUSTER GALAXIES AT HIGH REDSHIFT

Abstract: We present deep J and K s band photometry of 20 high redshift galaxy clusters between z = 0.8−1.5, 19 of which are observed with the MOIRCS instrument on the Subaru Telescope. By using nearinfrared light as a proxy for stellar mass we find the surprising result that the average stellar mass of Brightest Cluster Galaxies (BCGs) has remained constant at ∼ 9 × 10 11 M ⊙ since z ∼ 1.5. We investigate the effect on this result of differing star formation histories generated by three well known and independent stell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
177
6

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(214 citation statements)
references
References 94 publications
29
177
6
Order By: Relevance
“…Mortlock et al 2011). This lack of evolution in the massive galaxy population is consistent with studies of brightest cluster galaxies (BCGs) in which little change is observed in BCG stellar masses to redshifts of z ∼ 1−1.5 (Stott et al 2010). These observations corroborate the picture of galaxy evolution whereby a mass-dependent shut-down of star formation is experienced by galaxies (e.g.…”
Section: Redshiftsupporting
confidence: 87%
See 1 more Smart Citation
“…Mortlock et al 2011). This lack of evolution in the massive galaxy population is consistent with studies of brightest cluster galaxies (BCGs) in which little change is observed in BCG stellar masses to redshifts of z ∼ 1−1.5 (Stott et al 2010). These observations corroborate the picture of galaxy evolution whereby a mass-dependent shut-down of star formation is experienced by galaxies (e.g.…”
Section: Redshiftsupporting
confidence: 87%
“…Mullis et al 2005;Stanford et al 2005Stanford et al , 2006Stott et al 2010;Fassbender et al 2011). Such observations have acted to stimulate significant progress in our understanding of galaxy formation processes, in particular highlighting the importance of feedback processes in shaping the pace and form of the growth of galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of stellar mass already in place for these galaxies at this redshift is immense considering the short period of time that they have had to form their stellar content. These stellar masses approach those of z ∼ 1 BCGs (e.g., Stott et al 2010;Lidman et al 2012;Ascaso et al 2014), astounding considering these galaxies have ∼4 Gyr to evolve between the redshift of Cl J0227-0421 and that of z ∼ 1 cluster samples. The presence of these massive galaxies within Cl J0227-0421 appears, at least at the surface, to be consistent with the results of Diener et al (2013), in which an excess of massive galaxies was found within protocluster candidates in the COSMOS field at slightly lower redshifts (1.8 < z < 3.0) and in slightly less massive structures (σ v = 30−550 km s −1 ).…”
Section: The Density Of Massive Galaxies In CL J0227-0421mentioning
confidence: 66%
“…Observed K-band magnitude of brightest-cluster galaxies (shown as "+") and radio galaxies (shown as "x") as a function of redshift (plot reproduced from Lidman et al 2012). Some of the data points were taken from Stott et al (2008Stott et al ( , 2010. The large red stars illustrate that TXS 2353−003 and NVSS J210626−314003 fall well within the expected range of K-band magnitude, and also have typical K-band magnitudes for HzRGs at their redshifts (black crosses; Seymour et al 2007; see also De Breuck et al 2002;Willott et al 2003;Bryant et al 2009).…”
Section: K−z Relationshipmentioning
confidence: 99%